Implementasi Kurikulum 2013 Terhadap Kinerja Guru di Sekolah Dasar Islam Darussalam Bekasi - Aji Zul Arffan; Abdul Kosim; Kasja Eki Waluyo (Jurnal Ilmiah Wahana Pendidikan, 2022)
The curriculum is a collection; content, goals, and methods used by teachers to achieve educational goals in schools. This study aims to determine the performance of teachers and the obstacles faced by Darussalam Islamic Elementary School teachers in implementing the 2013 Curriculum. To achieve this goal, this study used a descriptive qualitative approach. The results of the study show that: (1) The ability of teachers in planning, implementing, and evaluating the 2013 Curriculum is good but not optimal in planning, learning processes and assessments, especially time management which learning is less effective and the use of the 2013 curriculum assessment is not yet authentic. (2) The motivation of teachers in implementing the 2013 curriculum is already high, seen from the implementation of tasks, moral responsibility in teaching, and the need for cooperation. (3) The commitment and responsibility of teachers in implementing the 2013 curriculum also looks good by showing high personality, dedication, and loyalty to teaching assignments. (4) supporting and inhibiting factors in the implementation of the 2013 Curriculum include: (a) the coordination carried out by the principal for the realization of the implementation of the 2013 curriculum is on target (b) good communication between various parts in the implementation of the 2013 Curriculum has been carried out (c) but the supervision of the principal and assistant teachers of the Darussalam Islamic Elementary School teachers has not been optimal in the learning and assessment process